Co-precipitation method for the preparation of fine ferroelectric BaBi2M2O9 - Gaikwad, S. P.; Potdar, HS; Samuel, V; Ravi, V (Ceramics International, 2005)
A simple co-precipitation technique had been successfully applied for the preparation of pure fine powders of single phase BaBi2Nb2O9. Ammonium hydroxide and ammonium oxalate were used to precipitate Ba2+, Bi3+ and Nb5+ cations simultaneously. No pyrochlore phase was formed while heating powder at 800 degrees C and pure BaBi2Nb2O9 phase was found to be formed by X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 100. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders chemical preparation

Coprecipitation technique to prepare BaNb2O6 - Natarajan, N; Samuel, V; Pasricha, R; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
A mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and niobium ions as barium oxalate and niobium hydroxide under basic conditions. This precursor on calcination at 750degreesC yielded BaNb2O6 ceramics. This is a much lower temperature as compared to that prepared by traditional solid-state method (1000degreesC), as reported for the formation of BaNb2O6. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ammonia; Ceramics; Electron microscopy; niobium oxide; Oxides

Low temperature synthesis of MgTa2O6 powders - Navale, SC; Samuel, V; Ravi, V (Materials Letters, 2005)
A combination of digestion and further low temperature calcination to crystallize the product is employed to prepare MgTa2O6 (MT) ceramics. Freshly prepared niobium hydroxide gel is mixed with magnesium hydroxide thoroughly and allowed to react at 100 degrees C under refluxing and stirring conditions for 6-12 h. The X-ray amorphous product so formed is heated at 550 degrees C to form crystalline MgTa2O6. This is the lowest temperature so far reported for the formation of MgTa2O6. For comparison, MT powders were also prepared by the traditional solid state method. Transmission electron microscope (TEM) investigations revealed that the average particle size is 40 nm for the low temperature calcined powders. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; magnesium tantalate; Oxides; X-ray diffraction

Preparation of nanocrystalline ferroelectric BaNb(2)O6 by citrate gel method - Gaikwad, S. P.; Samuel, V; Pasricha, R; Ravi, V (Bulletin of Materials Science, 2005)
A gel was formed when a aqueous solution of BaCl2, NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600 degrees C yielded the nano crystallites of BaNb2O6, as confirmed by X-ray diffraction study (XRD). This is a much lower temperature as compared to that prepared by traditional solid state method (1000 degrees C) as reported for the formation of BaNb2O6. Transmission electron microscopic. (TEM) investigations revealed that the average particle size is 50 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1000. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides

Preparation of nanocrystalline LiNbO3 by citrate gel method - Navale, SC; Samuel, V; Ravi, V (Materials Letters, 2005)
A gel was formed when an aqueous solution of Li(NO3) NbF5 and citric acid in stoichiometric ratio is heated in a water bath at 100 degrees C. This gel on decomposition at 700 degrees C produced the fine crystallites of ternary oxide, LiNbO3 (LN). The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; electronic materials; lithium niobate; X-ray diffraction

Preparation of ultrafine LiTaO3 powders by citrate gel method - Navale, SC; Samuel, V; Ravi, V (Bulletin of Materials Science, 2005)
A gel was formed when a aqueous solution of Li(NO3), TaF5 and citric acid in stoichiometric ratio was heated in a water bath. This gel on decomposition at 700 degrees C produced fine crystallites of ternary oxide, LiTaO3 (LT). The phase contents and lattice parameters were studied by powder X-ray diffraction (XRD). Particle size and morphology were studied by transmission electron spectroscopy (TEM).
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction

Synthesis of nanocrystalline rutile - Samuel, V; Pasricha, R; Ravi, V (Ceramics International, 2005)
Nanocrystalline titanium dioxide (TiO2) in the rutile phase has been obtained by homogeneous precipitation using urea and TiOCl2. A mixture of urea and TiOCl2 is heated on a hot water bath at 65-75 degrees C to precipitate rutile powders. X-ray diffraction (XRD) studies on these oven-dried powders indicated the formation of single-phase rutile. Raman scattering experiments were also performed to confirm the formation of the rutile phase. Transmission electron microscopy (TEM) investigations revealed the average particle size of these powders to be 40 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical preparation; Electron microscopy; powders; TiO2; X-ray methods

Coprecipitation technique to prepare NaNbO3 and NaTaO3 - Samuel, V; Gaikwad, A. B.; Ravi, V (Bulletin of Materials Science, 2006)
A simple coprecipitation technique has been used successfully for the preparation of pure, ultrafine, single phases of NaNbO3 (NN) and NaTaO3 (NT). An alcoholic solution of ammonium carbonate and ammonium hydroxide was used to precipitate Na+ and Nb5+ (or Ta5+) cations under basic conditions as carbonate and hydroxide, respectively. On heating at 700 degrees C, these precursors produce respective products. For comparison, both NN and NT powders were also prepared by the traditional solid state method. The phase purity and lattice parameters were studied by powder X-ray diffraction (XRD). The particle size and morphology were studied by scanning electron microscopy (SEM).
Keywords: Ceramics; Chemical synthesis; Electron microscopy; electronic materials; Oxides; X-ray methods